2012
DOI: 10.1111/ppa.12017
|View full text |Cite
|
Sign up to set email alerts
|

Fast real‐time detection of Potato spindle tuber viroid by RT‐LAMP

Abstract: This paper reports the development of a single tube, real-time, reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting Potato spindle tuber viroid (PSTVd), one of the quarantine pathogens of potato in Europe and North America. The method enables detection of a broad range of PSTVd isolates, and is about 10 times more sensitive than the conventional reverse transcription polymerase chain reaction (RT-PCR) assay. Its benefits are not only its speed (15-25 min to obtain results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 33 publications
0
40
0
1
Order By: Relevance
“…Oligonucleotides (Thermo Scientific, Schwerte, Germany) were HPLC purified. PCR primers were designed as previously described (22), and LAMP primers were designed according to Lenari et al (23). The isolated RNA was reverse transcribed into ssDNA using reverse primers and Maxima Reverse Transcriptase (Thermo Scientific).…”
mentioning
confidence: 99%
“…Oligonucleotides (Thermo Scientific, Schwerte, Germany) were HPLC purified. PCR primers were designed as previously described (22), and LAMP primers were designed according to Lenari et al (23). The isolated RNA was reverse transcribed into ssDNA using reverse primers and Maxima Reverse Transcriptase (Thermo Scientific).…”
mentioning
confidence: 99%
“…LAMP is a highly specific and rapid technique, and it also circumvents the sensitivity of PCR and qPCR to inhibitors in plant extracts (Francois et al 2011); furthermore, its isothermal nature provides the potential for it to be deployed in the field (Kogovšek et al 2015;Tomlinson et al 2010a). LAMP has shown a comparable or better performance to other detection methods and a wide applicability for the detection of plant pathogenic bacteria (Lenarčič et al 2014), viroids (Lenarčič et al 2013), fungi (Tomlinson et al 2010b) and phytoplasmas (Bekele et al 2011;Dickinson 2015;Hodgetts et al 2011;Kogovšek et al 2015;Tomlinson et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Boonham et al (2004) found that the real time RT-PCR was 1000 times more sensitive than the chemiluminescent hybridization detection of PSTVd and it could detect up to 1 ×10 -6 dilutions of infected RNA. Later, the same method was used by Lenarcic et al (2012) who reported that the sensitivity was found up to 10 PSTVd RNA copies. Similarly, the detection limit of the realtime RT-PCR assay developed by Botermans et al (2013) was 2.5× 10 -5 dilutions (serial dilutions of infected tomato leaf sap in healthy tomato leaf sap).…”
Section: Discussionmentioning
confidence: 85%